The newspaper and serial holdings of the Immigration History Research Center, University of Minnesota
Part 1: Ukrainian American periodicals. - 1984. - 107 p. Part 2: Italian- American periodicals. - 1985. - 55 p. Part 3: Finnish-American periodicals, Baltic-American periodicals, West Slavic-American periodicals, East Slavic-American periodicals. - 1985. - 233 p.